Accessibility and Reliability of Expert Evidence in Civil Environmental Cases in Indonesia and Netherland: A Preliminary Survey - Cecep Aminudin; Efa Laela Fakhriah (International Journal of Supply Chain Management, 2022)
Expert evidence has a role in assisting the court to understand the scientific aspect of environmental cases. This paper describes as a preliminary survey on the existing rules and judicial practice on expert evidence in Indonesia and Netherland from the perspective of accessibility and reliability. Accessibility issue connected with expert appointment, fees and immunity. While reliability issue related with the expert appointment, qualification, objectivity, impartiality and report quality. Both jurisdictions regulates expert evidence in its civil procedural law with different level of elaboration in term of expert appointment and its subsequent rules such as expert report, procedure for investigation, compensation and honorarium, impartiality and objectivity assurance which could predispose the court settlement of environmental cases in practice. For historical reason, the rule on court appointed expert and party expert in the Dutch civil procedural law and its development could be learned for future development of Indonesia civil procedural law and specific guideline such as for environmental cases in view of fairness in truth seeking in adjudication.